2018
DOI: 10.15407/hftp09.04.404
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent materials based on organic salts pyrolyzed at the silica surface

Abstract: Recently, specific carbon-based nanomaterials (quantum dots, CDs) became highly attractive due to their low toxicity, good biocompatibility, chemical inertness, high photostability and fluorescence. Doping with some heteroatoms was found to be an effective approach to improve their luminescence. Besides, using the surface of silica as a support might facilitate the nanodots formation and expand the application area of carbon-silica composites. Recent advancements in synthesis of luminescent silica/CDs composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Besides, it has been shown that silica gel glasses produced from silicate carboxylate precursors exhibit high PL characteristics [13]. Recent advancements in synthesis and analysis of silica/CDs composites revealed great potential of such systems in bioimaging, sensor, as well as solid-state lighting applications, and depending on the synthesis methods and the precursors used, it is possible already to achieve the PL QY from typically 7-14 up to 60% [14][15][16][17][18][19][20][21][22]. Table 2 gives the PL characteristics of some carbon-containing silica-based materials synthesized using various methods.…”
Section: -4mentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, it has been shown that silica gel glasses produced from silicate carboxylate precursors exhibit high PL characteristics [13]. Recent advancements in synthesis and analysis of silica/CDs composites revealed great potential of such systems in bioimaging, sensor, as well as solid-state lighting applications, and depending on the synthesis methods and the precursors used, it is possible already to achieve the PL QY from typically 7-14 up to 60% [14][15][16][17][18][19][20][21][22]. Table 2 gives the PL characteristics of some carbon-containing silica-based materials synthesized using various methods.…”
Section: -4mentioning
confidence: 99%
“…Table 2 gives the PL characteristics of some carbon-containing silica-based materials synthesized using various methods. -Pyrolysis of citric acid (thio)ureates at the fumed silica surface 7-11 [22] Most of the synthetic methods are still relatively complex and costly or the materials produced possess relatively low PL QY. In [22], the simple and inexpensive route to produce luminescent silica-based nanomaterials was used: citric acid ureates were deposited from aqueous or ethanol solutions onto fumed silica surface.…”
Section: -4mentioning
confidence: 99%
See 1 more Smart Citation